Synthesis of beta-amino alcohols from aromatic amines and alkylene carbonates using Na-Y zeolite catalyst - Shivarkar, Anandkumar B.; Gupte, Sunil P.; Chaudhari, Raghunath V. (Synlett, 2006)
A simple, efficient, and environmentally benign methodology for the synthesis of beta-amino alcohols from aromatic amines and alkylene carbonates in the presence of the highly active and reusable solid base catalyst Na-Y zeolite is demonstrated.
Keywords: Alkylation; alkylene carbonate; Amine; Amino alcohols; zeolite

Highly efficient sulfimidation of 1,3-dithianes by Cu(I) complexes - Giribabu, Lingamallu; Singh, Surya P.; Patil, Nandkumar M.; Kantam, M. Lakshmi; Gupte, Sunil P.; Chaudhari, Raghunath V. (Synthetic Communications, 2008)
A series of four Cu(I) complexes were tested for sulfimidation of 1,3-dithianes in the presence of [N-(p-tolysulfonyl)imino]phenyliodinane (PhI = NTs) as the nitrene-transfer agent. Cu(TMPhen)(PPh3)Br is an efficient catalyst with more than 90% yield of the corresponding product with less reaction time as compared to the literature copper(I) complexes.
Keywords: 1; 3-dithianes; Cu(I) complexes; PhI = NTs; sulfimidation

Highly selective synthesis of mono-ethylene glycol phenyl ethers via hydroxyalkoxylation of phenols by cyclic carbonates using large pore zeolites - Kinage, Anil K.; Gupte, Sunil P.; Chaturvedi, Rajiv K.; Chaudhari, Raghunath V. (Catalysis Communications, 2008)
Hydroxyalkoxylation of phenols by cyclic carbonates catalyzed by alkali loaded large pore zeolites has been reported. The study shows that KL type zeolite was recyclable and selective in producing mono-ethylene glycol pheryl ethers in similar to 98.5% yield. Various substituted simple phenols were converted into mono-ethylene glycol ether of phenols with over 90% yields, except 3-bromo and 2-methyl phenols. Mono hydroxyl plienols such as hydroquinone, biphenol and BPA (2,2-bis(4-hydroxyphenyl)propane) also produce corresponding mono- and di-ethylene glycol ethers. The ratio of ethylene carbonate to phenol was found to be critical for selective formation of monoethylene glycol phenyl ether of phenols. A ratio of two results in formation of appreciable amount of diether derivative viz., 2-(2-phenoxyethoxy) ethanol. Compared to ethylene carbonate, a lower reactivity of 1,2-propane carbonate was found for hydroxyalkoxylation of phenol. It was found that ring opening at less hindered methylene carbon of 1,2-propylene carbonate prevailed giving rise to selective formation of beta-hydroxy phenyl ethers. The reactivity of ethylene carbonate towards O-alkylation versus transesterification of phenol has been explained on the basis of HSAB concept. Finally, it has been shown that yield of mono-ethylene glycol phenyl ether is controlled both by basicity and channel architecture of zeolite structure. KL zeolite was found to be the most effective zeolite because of it's intermediate basicity and one dimensional channel architect. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: cyclic carbonate; ethylene glycol phenyl ether; hydroxyalkoxylation; phenol

Tandem synthesis of beta-amino alcohols from aniline, dialkyl carbonate, and ethylene glycol - Shivarkar, Anandkumar B.; Gupte, Sunil P.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2008)
An efficient tandem route for selective synthesis of beta-amino alcohols from anilines, dialkyl carbonate and ethylene glycol in the presence of recyclable Na-Y zeolite has been demonstrated. Transesterification of dialkyl carbonate by ethylene glycol produce ethylene carbonate which further reacts with aniline to give beta-amino alcohols in a single step. This reaction system was studied under high-pressure as well as pot reaction condition. Various process parametric effects were investigated for the reaction of aniline, dialkyl carbonate, and ethylene glycol. It was observed that a maximum 51% yield of mono-beta-amino alcohol, i.e., N-phenylethanolamine (NPEA). is obtained under pressure conditions. The yield of NPEA was improved drastically (>91%) by carrying out the reaction under pot conditions using diethyl carbonate as transesterification agent. Finally activity and selectivity of solid catalyst was explained on the basis of nature of active sites and pore structure of the catalyst.

Catalytic synthesis of chalcone and flavanone using Zn-Al hydrotalcite adhere ionic liquid - Kunde, Lalita B.; Gade, Swapna M.; Kalyani, Vishwanath S.; Gupte, Sunil P. (Catalysis Communications, 2009)
The Claisen-Schmidt condensation of 2'-hydroxy acetophenone and benzaldehyde to chalcone and flavanone show that calcined Zn-Al (6) hydrotalcite is active for this synthesis. Coating of ionic liquid `1-(tri-ethoxy-silyl-propyl)-3-methyl-imidazolium chloride' on Zn-Al hydrotalcites was accomplished employing incipient wetness process and on NaY, NaX, MK-5 and silica gel employing co-condensation methodology. Impregnated IL on calcined Zn-Al (6) catalysts were characterized by XRD, SEM, BET, (13)C and (27)Al NMR analysis and the activity of these catalysts were investigated for chalcone and flavanone synthesis. (27)Al CP MAS NMR technique was used to show that interaction of IL with hydrotalcite modifies the acid-base sites and is responsible for enhancement of catalyst activity. Several aromatic aldehydes were screened to assess the general applicability of the system. (c) 2009 Published by Elsevier B.V.
Keywords: (27)Al CP MAS NMR; chalcone; Claisen-Schmidt condensation; Flavanone; Ionic liquid; Zn-Al hydrotalcite

Dibutyltin oxide catalyzed aminolysis of oxalate to carbamate, oxamate and derivatives of imidazolidine trione - Kunde, Lalita B.; Kalyani, Vishwanath S.; Gupte, Sunil P. (Applied Organometallic Chemistry, 2010)
Catalytic aminolysis of oxalates by simple and substituted ureas has been shown to give carbamates, oxamates and derivatives of imidazolidine trione. Various substituted ureas and oxalates were screened to verify the applicability of the protocol. The role of dibutyltin oxide as catalyst, effect of solvent and reaction conditions on product distribution pattern has been discussed. Copyright (C) 2010 John Wiley & Sons, Ltd.
Keywords: Aminolysis; carbamate; derivative of imidazolidine trione; oxalate; oxamate; transfunctionalyzation; Urea

Heterogenized copper catalysts for the amination of arylhalide: synthesis, characterization and catalytic applications - Patil, Nandkumar M.; Gupte, Sunil P.; Chaudhari, Raghunath V. (Applied Catalysis A-General, 2010)
This research investigated the synthesis, characterization and catalytic activity of heterogenized copper complexes for the selective amination of aryl halides. Amination reactions using homogeneous copper catalyst systems are not generally selective and it is also difficult to recover the catalyst from the homogeneous system for recycling. To overcome these difficulties, our efforts were directed towards the development of cheaper heterogeneous catalyst systems, which can be easily recovered and recycled. Heterogenized analogs of the homogenous Cu complexes were prepared using two methods: (a) encapsulation of copper complexes in zeolite-Y and (b) tethering of copper complexes on various supports like zeolite-Y, silica, charcoal, or clay. The encapsulated and tethered copper catalysts on zeolite-Y were characterized using EPR, Diffused reflectance UV-vis, XRD, IAS, ICPES, SEM, and TEM. The results confirmed that the copper complexes were truly heterogenized in zeolite-Y support. Encapsulated and tethered copper complexes were tested for amination of aryl iodide. The effects of various reaction parameters were examined using tethered Cu(Phen)(PPh(3))Br-PTA-Y catalyst to determine optimum conditions. A recycle study of encapsulated and tethered Cu catalyst was carried out to test their robustness for possible commercial exploitation. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Amination; C-N coupling; Copper; heterogeneous catalysis; mesoporous materials

Immobilized palladium nanoparticles catalyzed oxidative carbonylation of amines - Didgikar, Mahesh R.; Roy, Debdut; Gupte, Sunil P.; Joshi, Sunil S.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2010)
Catalytic application of immobilized palladium nanoparticles for synthesis or ureas by oxidative carbonylation of amines has been investigated. This is the first report oil oxidative carbonylation of amines to ureas using immobilized palladium nanoparticles catalyst. The palladium nanoparticles were immobilized on a NaY zeolite support through 3-aminopropyl-trimethoxysilane (APTS) as anchoring agent. The [Pd]-APTS-Y catalyst along with NaI promoter showed high conversion and selectivity to the desired urea products over several amine compounds including ail example of an aliphatic amine precursor even at 333 K. The immobilized catalyst was easily separated and recycled several times without any loss of activity. The role of different solvents, iodide promoters, iodide to Pd ratio, concentration of substrates, and temperature on the overall yield of the reaction was also investigated.
Joint 7th International Symposium on Catalysis in Multiphase Reactors (CAMURE-7)/6th International Symposium on Multifunctional Reactors (ISMR-6), Montreal, CANADA, AUG 23-26, 2009

Oxidative carbonylation of amine using water-soluble palladium catalysts in biphasic media - Didgikar, Mahesh R.; Joshi, Sunil S.; Gupte, Sunil P.; Diwakar, Makarand M.; Deshpande, Raj Madhukar; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2011)
Application of water-soluble palladium catalysts for oxidative carbonylation of aniline to N,N' diphenyl urea (DPU) has been reported. The water-soluble palladium catalysts prepared from sulfonated N-containing ligands were found to be highly stable under reaction conditions and easily recyclable due to insoluble urea product in the reaction medium. This is in contrast to the sulfonated phosphine ligands, which are vulnerable to oxidation under reaction conditions, showing poor activity and stability. Commercially available as well as laboratory synthesized ligands were used for preparing water-soluble palladium catalysts, for oxidative carbonylation of aniline. The best activity was obtained for Pd complex with disodium 2,2'-bipyridine-4,4'-disulfonate (Bipy-DS) ligand. Under optimized conditions Pd(BipyDS)Pd(OAc)(2) catalyst gave TOF of similar to 210h(-1) with aniline conversion of similar to 97% with similar to 91% selectivity for N.N'-diphenyl urea. It was found that the catalyst was easily reusable up to five times, with negligible loss in the catalytic activity. The effect of reaction parameters was investigated and a plausible reaction mechanism has been proposed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Amine; Biphasic catalysis; Carbonylation; Urea; Water-soluble palladium catalyst

Environmentally benign synthesis of beta-hydroxy sulfides using cyclic carbonates catalyzed by large-pore zeolites - Upare, Pravin P.; Kinage, Anil K.; Shingote, Savita K.; Gupte, Sunil P. (Green Chemistry Letters and Reviews, 2012)
An efficient one-pot synthesis of beta-hydroxy sulfides from thiophenol and cyclic carbonates catalyzed by large-pore zeolites has been reported. Reaction of thiophenol with ethylene carbonate in the presence of the Na-X zeolite catalyst gave the highest yield of 2-(phenylthio)ethanol (100%), while reaction with propylene carbonate a highest yield of regioselective product 1-(phenylthio)propan-2-ol was obtained (97%). Enantiomerically pure 1,2-propylene carbonate gave highly regioselective and stereospecific phenylthiopropanol, demonstrating that original chirality of propylene carbonate is retained. A plausible mechanism has been proposed for zeolite-catalyzed transformation involving a chemoselective nucleophilic attack of thiophenoloxide ion onto the less-substituted carbon of cyclic carbonate. The Na-X zeolite catalyst is recyclable and provides advantages of green chemistry approach to the synthesis of beta-hydroxy sulfides without the use of any solvent.
Keywords: beta-hydroxy sulfide; ethylene carbonate; propylene carbonate; thiophenol; zeolite